Richmond burning : the last days of the Confederate capital - Lankford, Nelson D. (New York : Viking, 2002)
Chronicles the final days of the Confederacy in a portrait of the burning of Richmond, with scenes depicting the destruction of this proud Southern city and profiles of the individuals who played a key role.
Prologue: April 15, 1865 -- Citadel: Winter into Spring, 1865 -- Daily Bread: Late March -- Waiting: Late March -- A Day for Fools: Saturday, April 1 -- Sabbath Rest: Sunday, April 2, Morning -- A Fugitive Government: Sunday, April 2, Afternoon -- Flitting Shadows: Sunday, April 2, Evening -- Mad Revelry of Confusion: Monday, April 3, Darkness to First Light -- Cruel Cataclysm: Monday, April 3, Morning -- Requiem for Buried Hopes: Monday, April 3, Morning -- Burning: Monday, April 3, Morning to Afternoon -- Let It Burn: Monday, April 3, Afternoon to Evening -- Upon the Wings of Lightning: Tuesday, April 4 -- A Week in April: Tuesday, April 4, to Saturday, April 8 -- A Whirlwind Sweeping: Tuesday, April 4, to Saturday, April 8 -- Prayers for the President: Tuesday, April 4, to Sunday, April 9 -- Important Communications: Sunday, April 9, to Friday, April 14 -- The Order of the Day: Saturday, April 15, and After -- The Sorry Silence of a Conquered People: April into May -- Epilogue: Blunt and Withered Laurels.
Includes bibliographical references (p. 277-298) and index.
Keywords: Richmond (Va.) -- History -- Siege, 1864-1865.; Richmond (Va.) -- History -- Civil War, 1861-1865.